Arterial spin labeling–MR may be an alternative to SPECT for evaluating cerebral perfusion in patients with unilateral middle cerebral artery stenosis. (2nd August 2020) - Ya, Jingyuan; Zhou, Da; Ding, Jiayue; Rajah, Gary B.; Wu, Ye; Yang, Xiaoxu; Hou, Yaqin; Jin, Kexin; Pan, Liqun; Wu, Yu; Du, Jingwen; Ding, Yuchuan; et al.
ABSTRACT: Objective: Cerebral blood flow (CBF) mapping of single-photon emission tomography (SPECT) is considered a gold standard for evaluating cerebral perfusion. However, invasiveness, high costs and strict technical requirements can limit its clinical use. We aimed to evaluate the concordance of CBF maps obtained from SPECT and pseudo-continuous arterial spin labeling magnetic resonance (PCASL-MR) imaging for evaluating cerebral perfusion. Methods: PCASL-MR/SPECT-CBF maps were obtained from 16 eligible patients with unilateral middle cerebral artery stenosis (MCAS). Three slices (basal ganglia, semi-oval center and cerebellum) on both PCASL-MR and SPECT maps were divided into different regions of interest (ROIs) according to the ASPECT criterion, arterial territories, and cerebral hemispheres, respectively. The concordance of the two types of CBF maps and the specificity and sensitivity of PCASL-MR imaging on predicting regional hypoperfusion were calculated. Results: A total of 448 ROIs were divided according to the ASPECT criterion, 192 ROIs partitioned in accordance with arterial territories, and 96 ROIs delineated based on cerebral hemispheres were analyzed. PCASL-MR imaging exhibited 83.78% to 100% sensitivity, 90.19% to 95.83% specificity for detection of hypoperfusion. Qualitative analyses revealed a strong concordance between PCASL-MR and SPECT on reflecting regional cerebral hypoperfusion (Kappa coefficient = 0.662–0.920, p < 0.01). Semi-quantitative analysis by ΔCBF revealed moderate consistency (Spearman correlation coefficient = 0.610–0.571). Conclusions: Our findings suggest that PCASL-MR may be a promising non-invasive, inexpensive alternative to SPECT for evaluating cerebral perfusion accurately in patients with symptomatic MCAS.